2014
DOI: 10.1007/s12147-014-9128-8
|View full text |Cite
|
Sign up to set email alerts
|

Servicewomen’s Strategies to Staying Safe During Military Service

Abstract: Numerous studies have documented high rates of sexual harassment and sexual assault among servicewomen during military service. In this study, we qualitatively explore the strategies United States servicewomen employed to reduce their risk of violence exposure during their military service. Based on the analysis of 14 focus group discussions conducted from 2007 to 2010, we found that women used a number of protective strategies, including accessing networks of support, capitalizing on their status (linked to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Sexual objectification facilitates dehumanization of the target (Vaes, Paladino, & Puvia, 2011), and is linked to greater acceptance of common rape myths. These myths are rooted in the idea that sexual violence is a crime of attraction and not power, and that women "ask for it" and are complicit in bringing it on themselves (Cheney et al, 2015;Gartner & Sterzing, 2016;Spaccatini et al, 2019). These narratives were evident in our study, with many men and some women blaming harassment on women's dress choices, minimizing men's responsibility by blaming their biological make-up, or arguing that women are often oversensitive in interpreting comments.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Sexual objectification facilitates dehumanization of the target (Vaes, Paladino, & Puvia, 2011), and is linked to greater acceptance of common rape myths. These myths are rooted in the idea that sexual violence is a crime of attraction and not power, and that women "ask for it" and are complicit in bringing it on themselves (Cheney et al, 2015;Gartner & Sterzing, 2016;Spaccatini et al, 2019). These narratives were evident in our study, with many men and some women blaming harassment on women's dress choices, minimizing men's responsibility by blaming their biological make-up, or arguing that women are often oversensitive in interpreting comments.…”
Section: Discussionmentioning
confidence: 81%
“…Some women tried to minimize harassment by "dressing down" for VA appointments, which echoes strategies that servicewomen use during active duty to reduce their risk of exposure to violence (Cheney et al, 2015). As Cheney et al (2015) note, these strategies are effective in the short term by decreasing the immediate threat, but do not challenge victim blaming cultures that facilitate gender-based violence (indeed, victim blaming functions to maintain a gender hierarchy status quo; Kay, Jost, & Young, 2005;Spaccatini, Pacilli, Giovannelli, Roccato, & Penone, 2019). Further, these strategies are rooted in sexualized notions of women; eventually, women can come to "treat themselves as objects to be looked at and evaluated" (Cheney et al, 2015, p. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Cheney et al. () found that women in the military perform gender in a way that protects them from gender‐based violence, but fails to critique the larger patriarchal system. This mirrors the tendency of women in the MCDC who push the boundaries of gender roles (by participating alongside men), while accepting the broader pressures placed on women (wearing makeup, looking, and smelling nice).…”
Section: Resultsmentioning
confidence: 99%
“…Female servicemembers in particular experience unique challenges in assimilating to military culture (Cheney et al, 2015; Silva, 2008). Although women are typically exposed to slightly less active combat than men during military service (Portnoy et al, 2018; Street et al, 2009), growing evidence suggests that they may face much higher rates of harassment and feel less supported by fellow servicemembers in the context of a traditionally male‐dominated workplace that has historically valued masculine ideals (Burns et al, 2014; Street et al, 2009).…”
Section: Introductionmentioning
confidence: 99%